1970
DOI: 10.3329/agric.v8i2.7571
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Heterosis for Productive Traits in F<sub>1</sub> Brinjal (<i>Solanum melongena</i> L.) Hybrids

Abstract: The study was carried out to estimate magnitude of heterosis over better parent and standard check for some important characters in 15 crosses resulting from a half diallel mating design of 6 inbred lines of brinjal. Hybrid variety 'Tarapuri' was used as standard check. The parents and the hybrids were evaluated at the farm of Olericulture Division, HRC, BARI, during the winter season of 2008-2009. A randomized complete block design with three replications was used. Significant levels of heterosis were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 1 publication
11
6
0
Order By: Relevance
“…As the above F 1 hybrid recorded less number of days for days to 50% flowering, it might have contributed for early fruit harvest. These findings are in consonance with Chowdhury et al (2010) [1] and Suresh et al (2012) [13] . Pennada x Babajipet-2 took more number of days to final picking, while EC-169089 took the least number of days to final harvest.…”
Section: Fruit Borer Damage Percentagesupporting
confidence: 92%
“…As the above F 1 hybrid recorded less number of days for days to 50% flowering, it might have contributed for early fruit harvest. These findings are in consonance with Chowdhury et al (2010) [1] and Suresh et al (2012) [13] . Pennada x Babajipet-2 took more number of days to final picking, while EC-169089 took the least number of days to final harvest.…”
Section: Fruit Borer Damage Percentagesupporting
confidence: 92%
“…While, the hybrid (P 1 xP 4 ) had the largest heterosis values relative to their mid-parents and (P 1 xP 3 ) relative to their better parent for total chlorophyll and also the same hybrid (P 1 xP 3 ) relative to their mid-parents had the largest heterosis value for early fruit number and (P 2 xP 1 ) relative to their better parent for the same trait. These results were in agreement with those of Chowdhury et al (2010) who showed heterosis over better parent for fruit yield and Makani et al (2013) who studied heterosis over midparents and better parent for yield and its components in eggplant.…”
Section: Heterosis Degreesupporting
confidence: 92%
“…Heterosis breeding as a tool for genetic improvement in eggplant has been studied by several researchers. Heterosis over better parent was detected by Chowdhury et al (2010) for plant height and fruit yield; Patil et al(2011) for number of branches per plant; Makani et al (2013) studied heterosis over mid and better parent for plant height and fruit yield; Chowdhury et al (2010) for early fruit number and yield.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first documentation of male sterility by Joseph Gottlieb Kölreuter, who observed anther abortion within species and specific hybrids, cytoplasmic male sterility has been identified in over 150 plant species (Schnabel and Wise 1998;Hanson and Bentolila 2004;Chowdhury and Ahmad 2010).…”
Section: Introductionmentioning
confidence: 99%